2013
DOI: 10.12928/telkomnika.v11i4.1205
|View full text |Cite
|
Sign up to set email alerts
|

Power Balance AODV Algorithm of WSN in Agriculture Monitoring

Abstract: Keywords: jaringan sensor nirkabel (WSN), Ad hoc On-Demand Distance Vector (AODV), Power Balance AODV (PB-AODV), indikasi kekuatan sinyal diterima (RSSI) Abstract WSN (wireless sensor networks) is a kind of energy-constrained network, which has been widely

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This review identified several approaches for optimizing the power consumption in IoT solutions for smart farming. Among the identified solutions are the use of low energy protocols (e.g., BLE, ZigBee, Sigfox), reduction of data transmission in sensor nodes by an optimized duty cycle [ 177 , 178 , 192 ] and the use of message routing approaches that are more energy-efficient [ 72 , 193 ].…”
Section: Discussionmentioning
confidence: 99%
“…This review identified several approaches for optimizing the power consumption in IoT solutions for smart farming. Among the identified solutions are the use of low energy protocols (e.g., BLE, ZigBee, Sigfox), reduction of data transmission in sensor nodes by an optimized duty cycle [ 177 , 178 , 192 ] and the use of message routing approaches that are more energy-efficient [ 72 , 193 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Simulation of the proposed CCZ algorithm is carried out on NS-2 (version 2.32). The routing protocol used is AODV [1], [16]- [19] to route the data traffic in the Wireless Sensor Network based IEEE802.15.4 MAC and PHY protocol and the free space propagation model as the radio propagation model. The number of nodes is 16, deployed in a sensor field region of 100*100 m 2 .…”
Section: Simulation and Analysis 61 Simulation Modelmentioning
confidence: 99%
“…However, the traditional load balancing schemes only allow the users of overloaded macrocell to handover to the neighboring macrocells. Consequently, there will be no suitable neighboring cells to support the users' handover when the neighboring cells are also overload, and it also cannot alleviate the unbalanced problem [9][10][11].…”
Section: Introductionmentioning
confidence: 99%